Experimental and theoretical study on catalytic ozonation of humic acid by ZnO catalyst. Issue 4 (4th March 2017) - Turkay, Ozge; Inan, Hatice; Dimoglo, Anatoli
ABSTRACT: Ozonation and catalytic ozonation of humic acid (HA) in the presence of ZnO were examined in a batch scale reactor. The degradation of HA by catalytic ozonation was found to be much more effective than ozonation alone. The quantum chemistry calculations showed that the reaction of the O3 disproportionation on the surface of ZnO corresponds to the barrierless mechanism. The activation energy of the transition state formation was −5.25 eV. The active oxygen atom formed on the surface of ZnO was found as interacting with both water molecules and dissolved organic molecules, which might lead to further oxidizing reactions.